Pores-free aluminium alloy by efficient degassing ultrasonic treatments. (15th December 2021) - Abramov, V.O.; Abramova, A.V.; Bayazitov, V.M.; Nikonov, R.V.; Cravotto, G.
Abstract: Mechanical properties of aluminium alloy castings depend on the porosity caused by hydrogen inclusions. Ultrasonic treatment is an effective method of modifying the structure of aluminum alloys and degassing the aluminum melt. However, when casting aluminum melts into a mold, this degassing method can hardly be effectively applied on an industrial scale, since the transmission of ultrasonic vibrations through the mold is not very effective. The goal of our research was to develop reliable ultrasonic equipment to ensure the transmission of enough power into the molten metal and an optimal distribution of the acoustic field inside the casting during the solidification. In this paper, we describe the principles of construction and operation of ultrasonic equipment for degassing aluminum melt in mold casting processes. We demonstrated that ultrasonic treatment can be effectively used on an industrial scale for degassing the aluminium melt both before and during its pouring into moulds. We have modelled, designed, manufactured and tested two waveguide systems for processing the melt in the casting ladle and through the casting head. Both ultrasonic waveguide systems showed a high efficiency. Finite element calculations using COMSOL Multiphysics have shown, that when using a waveguide system in the form of an "inverted mushroom", intense acoustic fields are generated both under and above the «wings», so a large volume of the melt can be treated effectively. X-ray tomography studies highlighted the efficiency of the ultrasound-assisted degassing in the casting ladle that completely eliminates pores in the casting.